Traditional health practitioners’ management of HIV/AIDS in rural South Africa in the era of widespread antiretroviral therapy - Thembelihle Zuma; Daniel Wight; Tamsen Rochat; Mosa Moshabela (Global Health Action, 2017)
Background: Traditional health practitioners (THPs) have been identified as a key local resource in the fight against human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) in South Africa. However, their approaches to the treatment of people living with HIV (PLHIV) have been met with scepticism by some biomedical practitioners amid increasing access to antiretroviral therapy (ART). Objective: In light of this ambivalence, this study aims to document and identify treatment approaches of THPs to the management of illness among PLHIV in the current era of widespread access to ART. Methods: The study was conducted as part of a larger trial of Treatment as Prevention (TasP) in rural northern Kwa-Zulu Natal, intended to treat PLHIV regardless of CD4 count. Nine THPs were enrolled using purposive and snowballing techniques. Repeat group discussions, triangulated with community walks and photovoice techniques, were conducted. A thematic analysis approach was used to analyse the data. Results: Eight of the nine THPs had received training in biomedical aspects of HIV. THPs showed a multilayered decision-making process in managing illness among PLHIV, influenced by the attributes and choices of the THPs. THPs assessed and managed illness among PLHIV based on THP training in HIV/AIDS, THP type, as well as knowledge and experience in the traditional healing practice. Management of illness depended on the patients’ report of their HIV status or willingness to test for HIV. Conclusions: THPs’ approaches to illness in PLHIV appear to be shifting in light of increasing exposure to HIV/AIDS-related information. Importantly, disclosure of HIV status plays a major role in THPs’ management of illness among PLHIV, as well as linkage to HIV testing and care for their patients. Therefore, THPs can potentially enhance the success of ART for PLHIV when HIV status is known.